The Effect of Pitch Position Exercises and Progression/Constrainst Exercises on the Ability to Close Dribble Indoor Hockey in Unimed Hockey Club Men's Fostered Students - Muhammad Rey Denin Nasution; Amir Supriadi (Jurnal Pendidikan Jasmani (JPJ), 2022)
This study aims to look at close dribble skills through pitch position exercises and progression/constraint exercises on close dribble skills in hockey games for students assisted by the Unimed Hockey Club. The research method used was the One Group Pretest and Posttest Design experiment, namely experiments conducted in one group without a comparison group. The analysis technique in this study is the normality test, data homogeneity test and t test. The results of the data normality test obtained the results of the pretest data 0.093 and the post-test 0.200, so that it can be concluded that the data is normally distributed. The homogeneity test results obtained significant pretest and post-test data results of 0.079, so it can be concluded that the data is normally distributed. The results of testing the SPSS data obtained significant results of 0.000 <0.05 so that it can be concluded that there is an effect of pitch position training and progression/constrainst exercises.